Pharmacogenetics of Between-Individual Variability in Plasma Clearance of Bedaquiline and Clofazimine in South Africa . (29th January 2022) - Haas, David W; Abdelwahab, Mahmoud Tareq; van Beek, Stijn W; Baker, Paxton; Maartens, Gary; Bradford, Yuki; Ritchie, Marylyn D; Wasserman, Sean; Meintjes, Graeme; Beeri, Karen; Gandhi, Neel R; Svensson, Elin M; et al.
Abstract: Background: Plasma bedaquiline clearance is reportedly more rapid with African ancestry. Our objective was to determine whether genetic polymorphisms explained between-individual variability in plasma clearance of bedaquiline, its M2 metabolite, and clofazimine in a cohort of patients treated for drug-resistant tuberculosis in South Africa. Methods: Plasma clearance was estimated with nonlinear mixed-effects modeling. Associations between pharmacogenetic polymorphisms, genome-wide polymorphisms, and variability in clearance were examined using linear regression models. Results: Of 195 cohort participants, 140 were evaluable for genetic associations. Among 21 polymorphisms selected based on prior genome-wide significant associations with any drug, rs776746 ( CYP3A5∗3 ) was associated with slower clearance of bedaquiline ( P = .0017) but not M2 ( P = .25). CYP3A5∗3 heterozygosity and homozygosity were associated with 15% and 30% slower bedaquiline clearance, respectively. The lowest P value for clofazimine clearance was with VKORC1 rs9923231 ( P = .13). In genome-wide analyses, the lowest P values for clearance of bedaquiline and clofazimine were with RFX4 rs76345012 ( P = 6.4 × 10 −7 ) and CNTN5 rs75285763 ( P = 2.9 × 10 −8 ), respectively. Conclusions: Among South Africans treated for drug-resistant tuberculosis, CYP3A5 ∗ 3 was associated with slower bedaquiline clearance. Different CYP3A5 ∗ 3 frequencies among populations may help explain the more rapid bedaquiline clearance reported in Africans. Associations with RFX4 and CNTN5 are likely by chance alone. Abstract : In a cohort of patients treated for drug-resistant tuberculosis in South Africa, CYP3A5∗3 was associated with slower plasma bedaquiline clearance. Different CYP3A5 ∗ 3 minor allele frequencies among populations may help explain the more rapid bedaquiline clearance previously reported with African ancestry.